Cost‐Effectiveness of Water Promotion Strategies in Schools for Preventing Childhood Obesity and Increasing Water Intake. Issue 12 (20th November 2019) - Kenney, Erica L.; Cradock, Angie L.; Long, Michael W.; Barrett, Jessica L.; Giles, Catherine M.; Ward, Zachary J.; Gortmaker, Steven L.
Abstract : Objective: This study aimed to estimate the cost‐effectiveness and impact on childhood obesity of installation of chilled water dispensers ("water jets") on school lunch lines and to compare water jets' cost, reach, and impact on water consumption with three additional strategies. Methods: The Childhood Obesity Intervention Cost Effectiveness Study(CHOICES) microsimulation model estimated the cost‐effectiveness of water jets on US childhood obesity cases prevented in 2025. Also estimated were the cost, number of children reached, and impact on water consumption of the installation of water jets and three other strategies. Results: Installing water jets on school lunch lines was projected to reach 29.6 million children (95% uncertainty interval [UI]: 29.4 million‐29.8 million), cost 4.25 (95% UI: 2.74‐5.69) per child, prevent 179, 550 cases of childhood obesity in 2025 (95% UI: 101, 970‐257, 870), and save 0.31 in health care costs per dollar invested (95% UI: 0.15‐0.55). In the secondary analysis, installing cup dispensers next to existing water fountains was the least costly but also had the lowest population reach. Conclusions: Installating water jet dispensers on school lunch lines could also save almost half of the dollars needed for implementation via a reduction in obesity‐related health care costs. School‐based interventions to promote drinking water may be relatively inexpensive strategies for improving child health.